Fractional calculus operators with Appell function kernels applied to Srivastava polynomials and extended Mittag-Leffler function - Nisar, Kottakkaran Sooppy; Suthar, D. L.; Agarwal, R.; Purohit, S. D. (Advances in difference equations, 2020)
This article aims to establish certain image formulas associated with the fractional calculus operators with Appell function in the kernel and Caputo-type fractional differential operators involving Srivastava polynomials and extended Mittag-Leffler function. The main outcomes are presented in terms of the extended Wright function. In addition, along with the noted outcomes, the implications are also highlighted.